DEIKSIS DALAM FOLKLOR LISAN PADA MASYARAKAT DAYAK BENAEH - Kapaso, Kapaso; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractResearch on deixis in oral folklore on the Benaeh Dayak community s on the descriptive of the from and meaning of person deixis, place and time. This is in accordance with the formulation of the problem that is directly related to the research objejctives, namely: (1) describing the from of deixis, place, and time in the deixis of dayak benaeh community oral folklore as a textual learning model, and (2) describing the meaning of deixis in folklore oral Benaeh Dayak community. The analysis of the from of person deixis shows that persona deixis in the Dayak Benaeh folklore has the singular andÂ plural from of first person deixis, the second person is singular and plural, and the third person in singural. The first from of person deixis is singural and plural, the second person is singural and plural and the third single is referential and construction meaningful. The from of deixis in folklore means congnitive meanwhile the from of time in Dayak Benaeh folklore is referential.Â Â Keywords: Form, Meaning, Deixis, Person, Place, Time